PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TYPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 67 PEMATANG PUDU KECAMATAN PINGGIR - mawarni, Netti; Erlisnawati, Erlisnawati; syahrilfuddin, syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : Problems in this study can be formulated as follows Is the application of cooperative learning model NHT type can improve learning outcomes IPA Grade V SDN.67 Causeway Pudu Mandau sub Bengkalis. This study aims to improve the learning process and to improve learning outcomes IPA Grade V SDN.67 Causeway Pudu Mandau sub Bengkalis. As the subjects in this study were students of class V Causeway SDN.67 Pudu Mandau sub Bengkalis The measured variable is the use of cooperative learning model NHT whereas student learning outcomes as measured by student observation sheets and evaluation sheets. Based on the research that has been done, it was found that an increase in student learning outcomes IPA Class V SDN.67 Causeway Pudu Mandau sub Bengkalis, using cooperative learning model NHT conducted research. From the analysis of the data obtained by the average absorption of students in pre-cycle is 45.70%. in the first cycle the average absorption of students is 80%, in the second cycle the average absorption of students is 100%. Based on analysis of these data it can be concluded that through the implementation of cooperative learning model NHT type can improve learning outcomes IPA Grade V SDN.67 Causeway Pudu Mandau sub Bengkalis.Keywords : Kooperatif Learning Model Type Numbered Heads Together (NHT), Science Learning Outcomes.